Investor protection and stock market development. Empirical approach on the European Union case - Marius Cristian Miloş; Laura Raisa Miloş (Juridical Tribune, 2019)
A fundamental objective of stock market regulation is investor protection, which influences the stability and the degree of development of capital markets. We use eleven years (2006-2016) of panel data from the World Bank, on the evolution of minority shareholders' protection. This paper aims at understanding the connection between regulation and the development of capital markets, both for developed and emerging European Union countries. The results are consistent with some of the results from empirical research in law, demonstrating a positive link between investor protection and stock market development during the analyzed period, after controlling for other drivers of stock market development, such as GDP growth and level of taxation. The results outline the importance of stock market regulation, making clear that minority shareholder regulation and its enforcement should be further improved in the European Union member states.